Are ethical and green investment funds more resilient? - Laura-Dona Capotæa; Margherita Giuzio; Sujit Kapadia; Dilyara Salakhova (European Central Bank (ECB), 2022)
Funds with an environmental, social and corporate governance (ESG) mandate have been growing rapidly in recent years and received inflows also during periods of market turmoil, such as March 2020, in contrast to their non-ESG peers. This paper investigates whether investors in ESG funds react differently to past negative performance, making these funds less sensitive to short-term changes in returns. In the absence of an ESG-label, we define an ESG- or Environmentally-focused fund if its name contains relevant words. The results show that ESG/E equity and corporate bond funds exhibit a weaker flow-performance relationship compared to traditional funds in 2016-2020. This finding may reflect the longer-term investment horizon of ESG investors and their expectation of better risk-adjusted performance from ESG funds in the future. We also explore how the results vary across institutional and retail investors and how they depend on the liquidity of funds' assets and wider market conditions. A weaker flow-performance relationship allows funds to provide a stable source of financing to the green transition and may reduce risks for financial stability, particularly during turmoil episodes.
Keywords: G11; G23; Q56; C58; 330; investment funds; sustainable investments; green finance; climate risk